Being cross pressured-parents' experiences of the transfer from paediatric to adult care services for their young people with long term conditions: A systematic review and qualitative research synthesis. (March 2021) - Ludvigsen, Mette S.; Hall, Elisabeth O.C.; Westergren, Thomas; Aagaard, Hanne; Uhrenfeldt, Lisbeth; Fegran, Liv
Abstract: Background: Family members of young people (13–24 years) with long-term conditions tend to experience multiple challenges when their children transfer from paediatric to adult care, as do the patients themselves. Objectives: To identify, interpret and theoretically conceptualise the meaning of parents' experiences of the transfer from paediatric to adult care of their young people with long-term conditions. Design: A qualitative research synthesis. Data sources: We obtained articles from Medline, CINAHL, PsycINFO, EMBASE, Scopus, and Web of Science. Unpublished theses and dissertations were searched for using Google Scholar, Mednar, and ProQuest Dissertations and Theses. Review methods: Based on a previously published protocol, we followed the guidelines from the Joanna Briggs Institute. Sandelowski and Barroso's qualitative research synthesis approach guided the metasynthesis. Articles published between 1999 and March 2019 were systematically searched for. Findings: Twenty-three reports from seven Western countries representing 454 parents including significant others such as aunts and grandparents of 462 young people with various diagnoses contributed to the review. 'Being cross-pressured' was the metasynthesis found to reflect parents' experiences of the transfer from paediatric to adult care of their young people with long-term conditions. The metasynthesis comprised four themes: 'Fluctuating between parental roles', 'Navigating contrasting healthcare contexts', 'Making decisions in the face of inner conflict', and 'Trusting their child's self-management ability'. Conclusions: Our metasynthesis finding of parents' experiences of being cross-pressured provides a new way of thinking about the study phenomena which is supported by transitions theory holding that multiple transitions can take place simultaneously involving myriads of concurrent and conflicting demands. The cross pressure may overwhelm parents. The clinical implications are to recognise parents' experiences and distress in healthcare planning to promote safe and predicable transfers of their young people. Provision of healthcare to parents during transfer needs to be tailored to a collaborative decision-making process between parents, their young people, and involved practitioners across paediatric and adult healthcare services. Tweetable abstract: Parents experienced being cross-pressured when their young people with long-term conditions were transferred from paediatric to adult care.